Assessing the impact of information technology in a power sector by fuzzy analysis of variance. (1st January 2014) - Azadeh, Ali; Talebi, Sahar
This paper assesses the multiple impact of information technology at the level of individual. Torkzadeh and Doll's 12-item instrument is used here, which measures how extensively information technology impact on four factors task productivity, task innovation, customer satisfaction and management control . So to assess the equivalency of information technology effect on different departments within the organisation, the analysis of variance is applied for each factor. The traditional ANOVA requires exact input data, but due to the complexity and uncertainty involved in real world problems, it is sometimes unrealistic or even impossible to require exact judgments. Consequently, a method called analysis of variance for fuzzy data is suggested. To verify the validity of the questionnaire, the convergent validity, discriminate analysis and reliability estimation tests are performed. Fuzzy ANOVA seems to be ideal for IT analysis in uncertain and ambiguous environment. It is furthermore superior to conventional approach for such environments.